Analysis of physiotherapists' perceptions about specialized professional training in the area of Traumato-orthopedics (Research, Society and Development, 2022)
The epidemiological profile of the population has been changing over the years, which has led to the emergence of diseases linked to the musculoskeletal system, whether due to repetitive strain, trauma, work activities, among other causes. As a result, the specialty in Trauma-Orthopedics has gained space. Therefore, the present article aimed to understand the specialty of Traumato-Orthopedic Physiotherapy and its importance for the current scenario in Brazil. This is a qualitative research, carried out through focus groups with physical therapists who did residency or postgraduate studies in the area of Trauma-Orthopedics. The interviews followed a semi-structured script and after data collection, the statements were analyzed using content analysis according to the Bardin technique. It is noticed that physical therapists see the importance of specialization in the area of ​​Trauma-Orthopedics for greater professional improvement, whether through residency or postgraduate courses, as well as, both allow the professional to theoretical training in the area, contributing to provide effective patient care. It is concluded that it is important to qualify the physiotherapist through Lato sensu postgraduate courses, as these provide the updating and improvement of the professional's technical skills and abilities.